ASSISTENCIALISMO NA DIMENSÃO CIDADANIA - SAÚDE DA HISTÓRIA A PRÁTICA COTIDIANA - Zuleika Maria Patrício; Ellen Jeane Schuldt; Andréa Silva; Dione Lucia Prim (Universidade Federal do Paraná, 2016)
Resumo